DIGITAL MARKETING COMMUNICATION STRATEGY VIA INSTAGRAM SOCIAL MEDIA - Finny Redjeki (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Marketing communications via internet media can provide benefits in various fields. The marketing process via internet media is able to make it easier for consumers to obtain the goods they want. One of the social media on the internet that is widely used by people as a marketing communication medium is Instagram. Through Instagram, business people can display photos or videos of their products or services so that they can attract consumer interest. Instagram marketing is a marketing activity carried out using all the facilities provided by Instagram with the aim of increasing sales and establishing better communication with consumers. In managing a marketing communication system, effective and efficient strategy design and sales programs are needed. Sales promotion is an important part of a company's marketing communications strategy and sales promotion is a marketing activity that proposes the added value of a product (to get more than the existing value of the product) over a certain period of time in order to encourage consumer purchases, sales effectiveness or encourage other efforts. carried out by sales personnel according to Hermawan.